Health-sector responses to intimate partner violence in low- and middle-income settings: a review of current models, challenges and opportunities - Manuela Colombini; Susannah Mayhew; Charlotte Watts (The World Health Organization, 2008)
There is growing recognition of the public-health burden of intimate partner violence (IPV) and the potential for the health sector to identify and support abused women. Drawing upon models of health-sector integration, this paper reviews current initiatives to integrate responses to IPV into the health sector in low- and middle-income settings. We present a broad framework for the opportunities for integration and associated service and referral needs, and then summarize current promising initiatives. The findings suggest that a few models of integration are being replicated in many settings. These often focus on service provision at a secondary or tertiary level through accident and emergency or women's health services, or at a primary level through reproductive or family-planning health services. Challenges to integration still exist at all levels, from individual service providers' attitudes and lack of knowledge about violence to managerial and health systems' challenges such as insufficient staff training, no clear policies on IPV, and lack of coordination among various actors and departments involved in planning integrated services. Furthermore, given the variety of locations where women may present and the range and potential severity of presenting health problems, there is an urgent need for coherent, effective referral within the health sector, and the need for strong local partnership to facilitate effective referral to external, non-health services.